Maldynia multidisciplinary perspectives on the illness of chronic pain - Giordano, James J. (Boca Raton : CRC Press, 2011)
"An in depth examination of maldynia, also known as chronic pain, this book explores pain as a bio-cultural phenomenon that necessitates reexamination of medical philosophy, ethics, education, and practice. It provides a historical account of pain and then frames it with contemporary neurobiological perspectives. This book supplies a foundation upon which to illustrate (1) how what we know about pain could and should influence medical education, and the scope, and value (s) of medical practice, and (2) how a knowledge of the history and present considerations of pain might help to construct meaningful, patient-centered medicine"--Provided by publisher.
ch. 1. Maldynia : the illness of chronic pain / James Giordano -- ch. 2. A short history of pain and its treatment / M. Alexandra Valadas -- ch. 3. Pain does not suffer misprison : the presence and absence that is pain / James D. Katz -- ch. 4. Understanding suffering : the phenomenology and neurobiology of the experience of illness and pain / Peter A. Moskovitz -- ch. 5. How (can) I feel your pain : the problem of empathy and hermeneutics in pain care / Giusi Venuti -- ch. 6. Spirituality, suffering, and the self / James Giordano and Nikola Boris Kohls -- ch. 7. Expressions of chronic pain and suffering in Western art / Scott L. Karakas -- ch. 8. Maldynia as muse : a recent experiment in the visual arts and medical humanities / Nathan Carlin and Thomas Cole -- ch. 9. Maldynic pain in image and experience : engraving meaning through subtraction / Rosemary Feit Covey -- ch. 10. Musical representations of physical pain / Elaine Peterson -- ch. 11. Beyond technology : narrative in pain medicine / Lucia Galvagni -- ch. 12. Psychological assessment of Maldynic pain : the need for a phenomenological approach / Michael E. Schatman -- ch. 13. Painism : a new ethics : Richard Ryder's moral theory and its limitations / Hans Werner Ingensiep -- ch. 14. Maldynia : chronic pain, complexity, and complementarity / James Giordano and Mark V. Boswell -- ch. 15. A clinical ethics of chronic pain management : basis, reason, and responsibilities / Edmund D. Pellegrino -- ch. 16. Children, Maldynic pain, and the creation of suffering : toward an ethic of lamentation / Carlos Gomez -- ch. 17. Goal-directed health care and the chronic pain patient : a new vision of the healing encounter / David B. Waters and Victor S. Sierpina -- ch. 18. The problem of pain and the moral formation of physicians / F. Daniel Davis.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Chronic pain; Chronic pain -- Social aspects; Electronic books